A membrane-anchored fluorescent probe for detecting K+ in the cell microenvironment. Issue 25 (8th March 2016) - Xiong, Mengyi; Zhu, Huijie; Rong, Qiming; Yang, Chan; Qiu, Liping; Zhang, Xiao-Bing; Tan, Weihong
Abstract : A membrane-anchored fluorescent probe for detecting K + in the cell microenvironment. Abstract : Cell-surface fluorescent probes are effective tools in cell biology and engineering. Here, we for the first time report a diacyllipid–aptamer conjugate-based fluorescent probe which could anchor on cell membrane for real-time tracking of potassium ions in the cell microenvironment.